Facilitating Language Acquisition Through Songs - RAHAL, MAISSA (My University, 2020)
Songs are appreciated for their linguistic, pedagogical, cultural and entertaining features and they are precious language learning materials and our case of study is the American corner (SHELF). They can be used to teach and develop every aspect of a language. This paper aims to verify these claims and confirm the effectiveness of using songs as a means to improve young learners’ English language vocabulary and to determine whether songs influence young learners’ motivation to learn English. The paper deals with theoretical explanations of young learners, listening skills, and different aspects of using and teaching songs. It also discusses how songs influence motivation and the connection of songs with some language learning theories. The analytical part of the paper explains the procedure and the results obtained from the pre-tests, post-tests and delayed tests for three different children’s songs as well as from the questionnaire that was done in order to collect information about motivation provided by songs. The results showed that songs have a positive influence on vocabulary retention of young learners. Whatever setting is used, aural or aural/visual, the results prove that songs are suitable for different learning styles, they encourage positive learning experience, and enhance their knowledge. Songs aid motivation and help learners develop a love for language learning. Students motivated in this way are imaginative, creative, and eager to learn and succeed.
STUDY CASE: The American corner
Keywords: Songs; ESL; Young Learners; Motivation; Vocabulary; Listening Skills